Employee Performance Analysis Review From Work Discipline And Communication - Sheren Slavia Yusup; Rita Tri Yusnita; Arga Sutrisna (Journal of Indonesian Management, 2022)
This research was conducted with the aim of analyzing employee performance in terms of Work Discipline and Communication at the Tasikmalaya City Personnel and Human Resources Development Agency. The method used in this study is a case study method using data obtained directly through questionnaires distributed to 61 respondents who are employees of the Tasikmalaya City Personnel and Human Resources Development Agency. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that Work Discipline and Communication simultaneously have a significant effect on Employee Performance. Work Discipline partially has a significant effect on employee performance. Communication partially has a significant effect on employee performance of the Tasikmalaya City Personnel and Human Resources Development Agency.